Avaliação cinética e potencial do Nb2O5 obtido a partir de um complexo de nióbio para formação do oleato de metila através da reação de esterificação do ácido oleico - Oliveira, Samuel Alves de (2014)
Among the heterogeneous catalysts materials made from niobium show up as an alternative to meet the demand of catalysts for biodiesel production. This study aims to evaluate the potential of a heterogeneous catalyst derived from a complex of niobium in the reaction of methyl esterification of oleic acid. The catalyst was synthesized after calcination at different temperatures of a niobium complex ((NH4)3[NbO(C2O4)3].H2O) generating a niobium oxide nanostructure with a different commercial niobium oxide used to synthesize the complex. The commercial niobium oxide, the complex niobium and niobium catalyst were characterized by thermogravimetry (TG and DTA), surface area analysis (BET), scanning electron microscopy (SEM) and X-ray diffraction (XRD), showing the catalyst has researched morphological and crystallographic indicating a catalytic potential higher than that of commercial niobium oxide characteristics. Factorial with central composite design point, with three factors (calcination temperature, molar ratio of alcohol/oleic acid and mass percentage of catalyst) was performed. Noting that the optimal experimental point was given by the complex calcination temperature of 600°C, a molar ratio alcohol/oleic acid of 3.007/1 and the catalyst mass percentage of 7.998%, with a conversion of 22.44% oleic acid in methyl oleate to 60 min of reaction. We performed a composite linear and quadratic regression to determine an optimal statistical point of the reaction, the temperature of calcination of the complex at 450°C, the molar ratio of alcohol/oleic acid 3.3408/1 and mass percentage of catalyst of 7.6833% . Kinetic modeling to estimate parameters for heterogeneous catalysis it set well the experimental results with a final conversion of 85.01% with 42.38% of catalyst and without catalyst at 240 min reaction was performed. Allowing to evaluate the catalyst catalytic studied has the potential to be used in biodiesel production